Integration of The SAMR Learning Model In Vocational Education - Muktiarni Muktiarni (Universitas Pendidikan Indonesia (UPI), 2021)
The development of technology that is increasing in learning requires teachers to use a systematic model in the learning process that is integrated with ICT. One model that can be used in the learning process is using the SAMR model, which is a model in the learning process by integrating technology comprehensively. This model was introduced by Dr. Ruben Puentedura, a consultant in the field of education. This model uses a hierarchy to describe the cognitive level that can be obtained by using technology as a tool in the learning process. The process of using technology in learning must be understood in the right proportion and according to needs. The use of technology must be able to support the expected goals. The integration of ICT in the vocational education system has an influence on the role of educators and students. With ICT, educators are expected to be able to become facilitators and collaborators in the teaching and learning process so that students can play a more active role